(untitled) - Nguyen, Vinh Phuc (Hà Nội, 1995)
This book introduce about natural and human resources, historry, economic sitituation, cultural and social aspects, visits-tourism...
Keywords: Hanoi (Vietnam),Hà Nội (Việt Nam),Vietnam,Việt Nam; Description and travel,Du lịch và mô tả,Description and travel,Du lịch và mô tả